The Uji Aktivitas Antibakteri Sediaan Gel Semprot Ekstrak Etanol Daun Sintrong (Crassocephalum crepidiodes) Terhadap Staphylococcus aureus Pada Luka Infeksi Diabetes Mellitus - Sipayung, Sry Anita; Natalia , Astriani; Meutia, Rena; Simanjuntak, Nerly Juli Pranita (Journal of Pharmaceutical and Sciences, 2025)
Background: Diabetes mellitus (DM) is a metabolic disorder that impairs wound healing. Wounds in diabetic patients tend to heal slowly due to high blood glucose levels that disrupt immune function and blood circulation. Long-term antibiotic use may lead to resistance, necessitating natural antibacterial alternatives such as sintrong leaves (Crassocephalum crepidioides), which contain flavonoids, polyphenols, saponins, and tannins with antibacterial activity. The ethanol extract of sintrong leaves was formulated into a spray gel for its advantages in wound application, including ease of use, sterility, and good penetration ability. Objective: This study aimed to formulate sintrong leaf ethanol extract into a spray gel at various concentrations (5%, 10%, 15%, 20%), evaluate its physical stability, and test its antibacterial activity against S. aureus. Methods: Sintrong leaf extract was obtained through 96% ethanol maceration and formulated into a spray gel using Carbopol 940 as the base. Stability evaluation included organoleptic, viscosity, pH, drying time, and spray pattern tests. Antibacterial activity was assessed using the disc diffusion method. Results: The spray gel exhibited good physical stability over 21 days of storage. Antibacterial testing showed inhibition zones with diameters of 8.05 mm (5%), 8.02 mm (10%), 8.44 mm (15%), and 9.57 mm (20%), indicating moderate effectiveness. The 20% concentration showed the highest inhibition, though lower than the positive control (1% clindamycin). Conclusion: Sintrong leaf ethanol extract can be formulated into a stable spray gel with antibacterial activity against S. aureus, demonstrating the highest efficacy at 20% concentration. This study presents a potential natural alternative for diabetic wound infection treatment.